The Influence of Physical Activity Levels and Physical Fitness Levels on the Motor Skills of Sports Students - Maharani Fatima Gandasari; Ghana Firsta Yosika (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Students in sports exhibit elevated levels of physical activity overall. Physical activity and fitness significantly enhance motor abilities and sports performance. Nonetheless, the extent to which physical activity and fitness levels influence the motor skills of sports students remains ambiguous. Objectives.This study aimed to assess the impact of physical activity and fitness levels on the motor skills of sports students. The research employed a descriptive method with a correlational design and a quantitative approach. Materials and Methods. This study employs the Purposive Sampling technique, which selects the research sample based on specific criteria to enhance the representativeness of the resulting data. The sample for this study comprised 33 students from Sports Coaching Education, including 19 males and 14 females, used observation, questionnaires, and documentation as data collection methodologies. The data analysis employed ANOVA statistics with a significance level of α < 0.05. Results. The study demonstrates that each variable is interconnected and exerts influence on one another. This is substantiated by the F-test significance results, which do not exceed 0.05. Conclusion. Physical activity and fitness levels substantially influence the motor skills of sports students. Consistent participation in sports enhances motor abilities and underscores the significance of physical activity and fitness in fostering students' motor development, demonstrating that commitment to a healthy lifestyle yields substantial advantages for student athletes.